Construction Material Management through Inventory Control Techniques - RathinaKumar, V; Lalitha Priya, K; kumar.I, Prasanna; Ravekumar, C (International Journal of Engineering and Technology, 2018)
Objectives: A research has shown that the construction materials account for more than 55%-60% of the total expenditure of a project. Efficient material planning plays a major role in the successful handing over of a project within the estimated cost and schedule. Methods: This paper mainly focuses on materials planning and inventory control as these are the major aspects of material management. S-curve analysis is performed to measure the fluctuation between estimated materials cost and market materials cost. The major reasons for this are identified by interviewing engineers and contractors. Inventory control techniques such as ABC classification as well as EOQ analysis are conducted. Findings: The result of the S-curve analysis show that the actual materials cost is higher than the planned materials cost in most cases. ABC and EOQ analysis are applied to maintain sufficient stock in inventory and any given point of time, to protect the materials in the inventory against damages, to reduce inventory holding costs, to overcome stock-out problems and to maintain the inventory in an optimal level. Sensitivity check is applied to the results of EOQ analysis. The stock-out of A class and B class material problems faced in the  construction site can be reduced by  the application of ABC classification and BOQ analysis. The total expenditure of inventory is less after the adoption of these simple inventory control techniques.  Conclusion: Instead of using costly software for inventory management, the engineers and contractors may use these simple inventory control techniques which are equally beneficial and economical.